(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the effective use of the amaranth plant introduced in our country and the new varieties created, the study of the characteristics of rich biologically active substances and the unique chemical composition of amaranth and their effective use in protecting human health. The integrated use of local new varieties, the organization of functional nutrition, the problems of creating biologically active food additives in combination with wheat groats and soy flour and their implementation in practice are covered. In order to determine the optimal new local varieties "O’zbekiston-M", "Andijon", "Marhamat", "Ulug’nor" for creating a special porridge for people engaged in heavy physical labor, the number of components in the seeds of new amaranth varieties was comparatively studied: the main nutrients, essential amino acids, macro- and microelements were studied. Based on the results obtained, a conclusion was made to use the varieties "O’zbekiston-M" and "Ulug’nor" for these purposes.